FACTOR-FAKTOR PENENTU STRUKTUR MODAL - Sartono, Sawal; Ratnawati, Tri (Program Doktor Ilmu Ekonomi, 2020)
In this article, a literature review on the determinants of capital structure is presented from research conducted, both in Indonesia and internationally, in recent years.Furthermore, the results of the review will conclude the factors that determine the capitalstructure that generally affects the company's leverage. From the results of the review, itis known that the variables that influence the capital structure are; Corporate tax rates,debt costs, dividend payout ratios, firm age, company size, growth opportunities,liquidity, non-tax shields, profitability, tangibility Keywords: Capital Structure; Leverage; Determining Factors